2011
DOI: 10.1002/adem.201080143
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering of a Semiautologous Arterial Vessels with Reconstructed Media and Intima, Longtime Tested In Vivo

Abstract: Goal was to engineer biological, arterial grafts with antithrombotic, autologous endothelial luminal surface combined with extraluminal smooth vascular muscle layer (VSMC) and to test in vivo. (1) Different decellularisation methods described in literature were compared to identify the most suitable one with focus on the preservation of extracellular fibre matrix. (2) Endothelial precursor cells (EPC), isolated from bone marrow and VSMC from small venous segments of donor animals were cultivated. Cells were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Thus, we hypothesized that early endothelialization of SIS leaflets, either by capturing circulating cells or by pre‐seeding SIS with EOCs, would limit the development of intimal hyperplasia on bioprosthetic venous valves while also providing antithrombogenic activity. Previous studies have demonstrated that EOCs can regulate platelet accumulation and coagulation factor activation similar to mature endothelial cells, and EOCs have been seeded onto vascular grafts to improve hemocompatibility . However, the utility of covering SIS with EOCs to reduce hyperplasia on SIS bioprosthetic venous valves had not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we hypothesized that early endothelialization of SIS leaflets, either by capturing circulating cells or by pre‐seeding SIS with EOCs, would limit the development of intimal hyperplasia on bioprosthetic venous valves while also providing antithrombogenic activity. Previous studies have demonstrated that EOCs can regulate platelet accumulation and coagulation factor activation similar to mature endothelial cells, and EOCs have been seeded onto vascular grafts to improve hemocompatibility . However, the utility of covering SIS with EOCs to reduce hyperplasia on SIS bioprosthetic venous valves had not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that EOCs can regulate platelet accumulation and coagulation factor activation similar to mature endothelial cells, 36 and EOCs have been seeded onto vascular grafts to improve hemocompatibility. 13,20,21,[37][38][39][40][41] However, the utility of covering SIS with EOCs to reduce hyperplasia on SIS bioprosthetic venous valves had not been investigated.…”
Section: Antibody Orientationmentioning
confidence: 99%
“…To ensure complete coverage of the tubular graft lumen, seeding is generally performed using multiple inoculations with manual or automated rotation, or by perfusing a cell suspension through the graft wall. 35,36,42,66,[79][80][81] …”
Section: Vascular Tissue Engineering Applications Using Eocsmentioning
confidence: 99%
“…In another study, tissue-engineered grafts were constructed by selectively seeding bone marrow-derived EOCs onto the lumen and vascular smooth muscle cells onto the exterior of decellularized vessels. 81 These constructs were cultured in a bioreactor with pulsatile flow for 7 days, then implanted as interpositional carotid grafts in canines. At 14 weeks, 9 out of the 10 seeded grafts were patent.…”
Section: Naturally Derived and Biodegradable Scaffoldingmentioning
confidence: 99%
“…Therefore, seeding procedure with incorporation of the cells inside the matrix using an injection moulding technique with a subsequent maturation process under physiological stimuli represents an effective method to establish coculture settings on a scaffold with desired size and shape. Other authors described the sequential seeding of a scaffold material with EC on the luminal surface surrounded by smooth muscle cells and fibroblasts on the outside (for example [14,15]). In this way cocultures of vascular cells are already initially seeded according to their arrangement in a native vascular wall.…”
mentioning
confidence: 99%